2019
DOI: 10.1038/s41590-018-0305-x
|View full text |Cite|
|
Sign up to set email alerts
|

Mosaic nanoparticle display of diverse influenza virus hemagglutinins elicits broad B cell responses

Abstract: The current influenza vaccine has the inevitable risk of antigenic discordance between the vaccine and the circulating strains, which diminishes vaccine efficacy. This necessitates new approaches that provide broader protection against influenza. Here, we design a vaccine utilizing the hypervariable receptor-binding domain (RBD) of virus hemagglutinin displayed on a nanoparticle (np) able to elicit antibody responses that neutralize H1N1 viruses spanning over 90 years. Co-displaying RBDs from multiple strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
284
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 254 publications
(289 citation statements)
references
References 73 publications
(97 reference statements)
5
284
0
Order By: Relevance
“…There are also ongoing efforts to broaden immune responses against the conserved receptor binding site within the more variable influenza HA head. A recently described strategy wherein HAs from 8 different strains were presented on a single mosaic VLP effectively promoted cross-reactive responses against the receptor binding domain [22]**.…”
Section: Introductionmentioning
confidence: 99%
“…There are also ongoing efforts to broaden immune responses against the conserved receptor binding site within the more variable influenza HA head. A recently described strategy wherein HAs from 8 different strains were presented on a single mosaic VLP effectively promoted cross-reactive responses against the receptor binding domain [22]**.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging strategy in vaccine development is to use symmetrical nanoparticles to display a viral antigen with multiple copies of the antigen displayed to the immune system (31,32,(57)(58)(59). Repetitive antigen arrangements on nanoparticle surfaces is thought to facilitate B cell receptor co-aggregation, triggering, and activation (60).…”
Section: Epitope Selection and Copy Number On Nanoparticle Scaffoldsmentioning
confidence: 99%
“…Repetitive antigen arrangements on nanoparticle surfaces is thought to facilitate B cell receptor co-aggregation, triggering, and activation (60). Studies have shown that multivalent viral proteins displayed on nanoparticles are more immunogenic than other platforms (31,57,58,61,62). Although the nanoparticle display of epitopes appears to be an emerging solution to invoke multivalent display, several factors must be considered, such as the identity, molecular size, density/spacing, and copy number of the epitope, as well as the size and type of nanoparticle scaffold.…”
Section: Epitope Selection and Copy Number On Nanoparticle Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, seasonal influenza virus infections or vaccinations typically provide limited protection against antigenically drifted strains. New ‘universal’ vaccine antigens are currently being developed to elicit broadly-reactive antibodies against conserved epitopes in the HA receptor binding site (RBS) (Giles and Ross, 2011; Kanekiyo et al, 2019) as well as the HA stalk region (Impagliazzo et al, 2015; Krammer et al, 2013; Yassine et al, 2015).…”
Section: Introductionmentioning
confidence: 99%